STRATEGI BRANDING KOPI SEKANAK “KOPI PARA RAJA“ - Rofii, Eva Amalia; Mikasari, Dewi Aurora; Syafruddin Rais (JURNAL MENATA, 2022)
This study reconnoiters how the richness and local wisdom of Malay culture are preserved through the taste of coffee which has its authentic philosophy so that it becomes a strong branding. Count on the marketing public relations strategy of pull, push and pass to build a brand awareness of "Kopi Para Raja". Using strategic marketing public relations which is called Three Ways Strategy to intricate on how the strategic planning being established. The research method using qualitative approach and case study method. Data collection techniques are in-depth interviews and literature study. The results of this study indicate that the Marketing public relations of Kopi Sekanak wants to instill the mindset of "Kopi Para Raja" into the minds of consumers which has come to the results in a successful partnership, bundling and marketing campaign by Kopi Sekanak, in the process of establishing the brand awareness. Thus the progression in maintaining the brand awareness starts from the phase of unknown brand to the initial brand of Kopi Sekanak has reached the stage of the awareness of consumers which means the success of Kopi Sekanak resulted from a synchronized marketing efforts to promote Kopi Sekanak , Kopi Para Raja as a coffee brand.